Colored decision process Petri nets: Modeling, analysis and stability - Clempner, Julio (Zielona Góra: Uniwersytet Zielonogórski)
In this paper we introduce a new modeling paradigm for developing a decision process representation called the Colored Decision Process Petri Net (CDPPN). It extends the Colored Petri Net (CPN) theoretic approach including Markov decision processes. CPNs are used for process representation taking advantage of the formal semantic and the graphical display.
Keywords: decision process; colored Petri nets; colored decision process Petri nets; stability; Lyapunov methods; optimization; game theory